Effects Of compatibilizers on mechanical properties of Pet/Pp blend - Abdul Razak, N. C. (2013)
In this work, the effects of two compatibilizers; maleic anhydride grafted polypropylene (PP-g-MAH) and maleic anhydride grafted styrene-ethylene/butylene- styrene (SEBS-g-MAH) for poly (ethylene terephthalate) (PET)/polypropylene (PP) blends were investigated. PET/PP blends were prepared using twin screw extruder followed by injection moulding with compatibilizer particles (2, 4, 6, 8 and 10 phr respectively). The incorporation of PP-g-MAH in the blends increased Young's modulus, tensile strength and flexural strength. While, impact strength of the blend were increased with the addition of the SEBS-g-MAH.